Transition from stromatolite to thrombolite fabric: potential role for reticulopodial protists in lake microbialites of a Proterozoic ecosystem analog - Bernhard, Joan M.; Fisher, Luke A.; Murphy, Quinne; Sen, Leena; Yeh, Heidi D.; Louyakis, Artemis; Gomaa, Fatma; Reilly, Megan; Batta-Lona, Paola G.; Bucklin, Ann; Le Roux, Veronique; Visscher, Pieter T. (Frontiers in Microbiology, 2023)
Prior observations suggest that foraminiferan protists use their reticulopodia (anastomosing pseudopodia) to alter sediment fabric by disrupting laminations of subtidal marine stromatolites, erasing the layered structures in an experimental setting. Because microbialites and foraminifera 2 are found in non-marine settings, we hypothesized that foraminifera living in lakes could also disrupt layered microbialite fabric. With this aim and using a variety of multidisciplinary approaches, we conducted field surveys and an experiment on microbialites from Green Lake (GL; Fayetteville, New York State, USA), which has been studied as a Proterozoic ecosystem analog. The lake is meromictic and alkaline, receiving calcium sulfate-rich water in the monimolimnion; it supports a well-developed carbonate platform that provides access to living and relict microbialites. The living microbialites grow from early spring to autumn, forming a laminated mat at their surface (top ~5mm), but a clotted or massive structure exists at depth (>~1cm). We observed a morphotype of "naked" foraminiferan-like protist in samples from GL microbialites and sediments; thus, considered the possibility of freshwater foraminiferan impact on microbialite fabric. Results of an experiment that seeded the cultured freshwater foraminifer Haplomyxa saranae onto the GL microbialite surface indicates via micro-CT scanning and anisotropy analysis that the introduced foraminifer impacted uppermost microbialite layering (n=3 cores); those cores with an added inhibitor lacked changes in anisotropy for two of those three cores. Thus, it remains plausible that the much smaller, relatively common, native freeform reticulate protist, which we identified as Chlamydomyxa labyrinthuloides, can disrupt microbialite fabrics on sub-millimeter scales. Our observations do not exclude contributions of other possible causal factors.